The Rhythm of Strategy A Corporate Biography of the Salim Group of Indonesia - Dieleman, Marleen (ICAS Publications Series, 2007)
This book provides a well-documented analysis of the strategy of the Salim Group, one of the largest family conglomerates in Southeast Asia. Using a multitude of sources, including interviews with the Salim family and Salim Group managers, the author provides a comprehensive corporate biography of this fascinating family firm. The Rhythm of Strategy: A Corporate Biography of the Salim Group of Indonesia criticises existing theories on ethnic Chinese firms and instead provides a more nuanced view of the evolution of a small migrant trading business into the largest family business group in Southeast Asia. It argues that the strategy of this group oscillated irregularly between a business model built on connections and a professional business model adapted to markets. Due to its size and closeness to the Suharto regime, the Salim Group has played an important role in shaping Indonesia's economy.